Phraseology verbal expression in the informative speech of the current spanish - Cervera Rodríguez, Ángel (2017)
The purpose of this work is to delimit the area of the phraseological units and explain the linguisticpragmatic character of verbal phraseological expressions in the informative speech of current Spanish. For the theoretical foundation, have been taken as a reference some of the most relevant studies on phraseology in order to differentiate the fixed, semifixed expressions and placements. After the set of examples of verbal phraseological units extracted from diverse mass media, one has proceeded to apply the syntactic, lexical-semantic and pragmatic procedures that operate in them so as to identify the degree of firmness and idiomatic correction. In short, the phraseological units analyzed not only contain a literal meaning, but also additional meanings acquired in the communicative context.